On some criteria of convexity for compact sets - Vyhovs'ka, I. Yu.; Zelinskii, Yu. B.; Tkachuk, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We establish some criteria of convexity of compact sets in the Euclidean space. Analogs of these results areextended to complex and hypercomplex cases.